Relationships among Charolais sire expected progeny differences and actual progeny performance in commercial herds - S.C. Clark; Daniel W. Moser; R.E. Williams (Kansas Agricultural Experiment Station Research Reports, 2003)
Data on Charolais-sired calves were analyzed to evaluate progeny performance related to sire expected progeny differences (EPD) in a large data set of commercial crossbred cattle in several herds across the United States. The traits analyzed were birth weight (n=3,554) and weaning weight (n=3,604) of crossbred progeny from nationally evaluated sires. Birth weight EPD and weaning weight EPD were evaluated as predictors of crossbred performance. Random regression coefficients were estimated for progeny birth weight on sire birth weight EPD of 1.03±0.09 lb/lb of birth weight EPD, and for progeny weaning weight, 0.66±0.11 lb/lb of weaning weight EPD. Published sire birth weight EPD and weaning weight EPD were averaged and weighted on published accuracy. The average weighted sire birth weight EPD was 0.86 lbs and weaning weight EPD was 16.06 lbs, with an average accuracy of 0.79 and 0.75, respectively. Correlations for effect of sire in commercial herds with published sire birth weight and weaning weight EPD were 0.59 and 0.39, respectively. Sire birth weight EPD and weaning weight EPD were positively related to actual progeny performance. Therefore, selection based upon sire EPD should result in change of crossbred progeny performance. This further validates use of EPD as a selection tool for birth weight and weaning weight in commercial herds. However, weaning weight response was lower than expected, possibly a result of management practices in commercial herds compared to purebred herds.
Keywords: Cattlemen& #x27; s Day; 2003; Kansas Agricultural Experiment Station contribution; no. 03-272-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 908; Beef; Charolais; EPD; Progeny performance